Association among placental 11β‐HSD2, PPAR‐γ, and NF‐κB p65 in small‐for‐gestational‐age infants: A nested case‐control study. (12th April 2020) - Fu, Lin; Bo, Qing‐Li; Gan, Yu; Chen, Yuan‐Hua; Zhao, Hui; Tao, Fang‐Biao; Xu, De‐Xiang
Abstract: Problem: 11β‐Hydroxysteroid dehydrogenase 2 (11β‐HSD2) catalyzes active glucocorticoids into their inactive products, preventing the passage of glucocorticoids into the fetus from maternal circulation. Peroxisome proliferator‐activated receptor (PPAR)γ is a member of the nuclear receptor superfamily that regulates the expression of placental 11β‐HSD2. Nuclear factor‐kappa B (NF‐κB) is a transcription factor that regulates inflammatory signaling. This study aimed to investigate the association among 11β‐HSD2, PPAR‐γ, and NF‐κB p65 in small‐for‐gestational‐age (SGA) infants. Method of study: Forty‐six SGA and 46 appropriate‐for‐gestational‐age (AGA) infants were enrolled in this study. Both newborns and placentas were weighed. Placental 11β‐HSD2 levels were measured using Western blotting. Placental PPAR‐γ and NF‐κB p65 were detected by immunohistochemistry. Placental inflammatory cytokines were evaluated by real‐time RT‐PCR. Results: 11β‐HSD2 levels were lower in SGA placentas than those in AGA placentas. Placental PPAR‐γ‐positive nuclei were less in SGA than those in AGA. By contrast, placental NF‐κB p65‐positive nuclei were more in SGA than those in AGA. The levels of CRP, TNF‐α, IL‐8, and IL‐1β, several inflammatory cytokines, were higher in SGA placentas. Correlation analysis showed that neonatal weight was positively associated with PPAR‐γ and 11β‐HSD2 in SGA placentas. By contrast, neonatal weight was inversely correlated with NF‐κB p65 in SGA placentas. 11β‐HSD2 was positively correlated with PPAR‐γ in SGA placentas. Conclusions: Inflammation‐associated downregulation of placental PPAR‐γ and 11β‐HSD2 may be involved in SGA.